The policy and practice of establishing healthy eating in preschool children in the Republic of Srpska, Bosnia and Herzegovina: a qualitative study - S. Stojisavljevic; B. Djikanovic; D. Stojisavljevic; D. Manigoda; J. Niskanovic (BMC Nutrition)
Abstract Background Healthy eating in preschools is a very important but challenging goal that can benefit from an adequate institutional and system approach. Five years ago, the Ministry of Education and Culture in the Republic of Srpska, Bosnia and Herzegovina, adopted a policy for healthy eating in preschools in the form of a rulebook and standards, whose use was not mandatory. The aim of this research was to determine the practices, perceptions, and experiences of preschool personnel related to the implementation of the abovementioned rulebook and standards. Methods We applied a qualitative research method and conducted six focus groups: three with teachers (n = 37) and three with managers in preschools (n = 19). The qualitative data were analyzed according to the Framework Method. Results We found that the practice of healthy eating in public preschool settings involves a certain number of facilitators and ongoing challenges. While there are no doubts that the existing rulebook and standards are facilitating efforts in establishing healthy eating in preschools, their implementation has not been an easy-going process, and they have encountered resistance that has appeared at several levels. The participants perceived cookers as resistant and “old-fashioned” in preparing meals, which was found to be a significant challenge that requires education training and ongoing supervision with support. Experiences with limited financial resources and rigid public procurement procedures make it difficult to obtain desired food items. All the participants agreed that long-term commitment is needed to achieve the full implementation of policy recommendations, together with tripartite and convergent education programs for personnel, parents, and children. Conclusion Promoting proper nutrition in preschools requires a holistic approach that addresses both feasibility and attitudes toward policies, continuous education for staff, creative strategies for implementing new eating habits, and overcoming financial challenges. Collaboration with parents and community stakeholders is crucial in creating a supportive environment for healthy eating habits in preschool settings.